Foreign direct investment and worker rights : a case study of a private security multinational in Mozambique. - Carvalho, Daniela Sampaio de (My University, 2009)
This article intends to contribute with the reflection upon the theories that link FDI with social and economical development. For this purpose, the meanings of the expression “human and economical development” will be briefly reviewed, and later it will be approached along the theories on the relation of FDI with development. The theories are used as a support in order to reach this article’s goal of pointing out the FDI impacts on labour conditions on the private security multinational G4S in Mozambique, thus examining the impacts of this sort of FDI towards the country’s human development.
Keywords: Foreign direct investment; Worker rights; Globalization; Mozambique